Students’ Perception and Performance in Computer-Aided Design Subject at John B. Lacson Colleges Foundation-Molo - Francisco, Salvador (JPAIR Multidisciplinary Research, 2009)
This study aimed to ascertain factors related to perception of and performance in Computer-Aided Design subject among Commerce students at John B. Lacson Foundation Maritime University-Molo, Iloilo City (JBLFMU). This descriptive study was limited to determining the perception of and performance in Computer-Aided Design as a required subject among Bachelor of Science in Commerce students. The respondents of this investigation were selected fourth year students taking Computer-Aided Design as their elective, who will be classified as to high school of origin, entrance test results, grades in Math and grades in English, and ratings in laboratory results. The data to be used in this study were gathered through the use of a 20-item performance test made by the researcher, and the students’ Form 137-A. The mean (X) and the standard deviation (SD) were used for descriptive statistics. The t test for independent sample was used to determine the significant differences between variables with two-level categories such as high school of origin. The participants of this study were 37 fourth year Commerce students taking Computer-Aided Design as their elective subject at JBLFMU-Molo, Iloilo City. Results revealed that a positive and but not significant correlation existed between the students’ perception of and performance in Computer-Aided Design.
Keywords: Students; perception; performance; computer-aided design; JBLFMU-Molo